Developmental Environments in Preschool Educational Organizations and Their Types - Lizakhan Avezovna Ibragimova; Zukhra Kayratdinovna Naimova; Venera Shimbergenovna Seytmuratova; Nazira Kayratdinovna Naimova (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study investigated the diverse types of developmental environments prevalent in preschool educational organizations and their impact on children's learning and development. Employing a mixed-methods approach, we conducted classroom observations, teacher and administrator interviews, and utilized standardized environmental rating scales to assess the quality of preschool environments across various settings. Qualitative data analysis revealed key characteristics of effective developmental environments, highlighting the interplay of physical space, materials, social interactions, and pedagogical approaches. Quantitative data analysis using the ECERS-R scale and questionnaire data provided objective measures of environmental quality and explored relationships between environmental features and perceived impact on children's learning. The findings offer valuable insights for educators and policymakers seeking to optimize preschool environments to foster holistic child development.